Postoperative sore throat: prophylaxis and treatment - Elvio Mazzotta; Suren Soghomonyan; Ling-Qun Hu (Frontiers Media S.A., 2023)
Postoperative sore throat (POST) is one of the most reported complications after general anesthesia with an incidence of as high as 60% which may impact patient satisfaction and increase the cost of treatment. The aim of this review is to summarize the currently accepted approaches and new trends intended to reduce the risk and increase the treatment efficacy of POST. Difficult intubation, traumatic intubation, and several other factors contribute to the development of POST. Endotracheal intubation using a stylet-loaded tube exerts excessive pressure on the anterior tracheal wall predisposing to mucosal trauma and contributing to development of POST. Pharmacological interventions are aimed at prevention, amelioration of symptoms, and treatment of POST. Medications suggested for this purpose include corticosteroids, topical sprays and creams, non-steroidal anti-inflammatory drugs (NSAID), and N-methyl-D-aspartate (NMDA) receptor antagonists. The use of video-laryngoscopes (VL) for endotracheal intubation improves the glottic view and increases the success rates with less force required to ensure adequate laryngoscopic view. Nevertheless, despite advances in laryngoscopic devices, the incidence of POST remains high. A novel intubation technique with endotracheal tube (ETT) rotation 180 degrees (ETT 180°) has been suggested to overcome stylet related injury and, possibly, decrease the POST. To date, no clinical trials have been conducted to test the efficacy of ETT 180° in reducing the incidence of POST. Undoubtedly, the suggested method deserves further investigation to determine its role in patient care.